DISRUPTIVE TECHNOLOGICAL INNOVATION AND PROFIT GROWTH OF SMALL SCALE ENTERPRISES IN EBONYI STATE (Journal of Global Accounting, 2025)
The study examined the relationship between disruptive technological innovation and profit growth of selected small scale enterprises in Ebonyi state. The specific objective was to ascertain the extent to which the adoption of artificial intelligence and the adoption of blockchain technology influence profit growth of small scale enterprises in Ebonyi state. This study adopted a survey research design. The population of the study consisted of 1,206 small-scale enterprises registered and operating within Ebonyi State. The sample size of 300 small scale business operators was determined using the Taro Yamane formula, which is commonly employed for calculating sample sizes in large populations. Primary data were collected through a structured questionnaire. Descriptive statistics, specifically frequency and mean, were used to analyse the research questions while Spearman's correlation analysis was employed to test the hypotheses at a 5% level of significance. The findings of the study revealed that: the adoption of artificial intelligence significantly and positively influences the profit growth of small-scale enterprises in Ebonyi state (rho= 0.215; p-value = 0.000); the adoption of blockchain technology significantly and positively influences profit growth of small-scale enterprises in Ebonyi state (rho= 0.234; p-value = 0.000). In conclusion, the adoption of disruptive technological innovations as they are increasingly reshaping traditional business models also improve profit level of small-scale enterprises in Ebonyi State by creating opportunities for small businesses to thrive in a competitive environment. The researcher’s therefore recommend that small-scale enterprise owners in Ebonyi state should invest in more advanced AI tools and training programs to enhance their understanding and application of artificial intelligence in business operations to achieve greater profit growth.
Keywords: Artificial Intelligence; Blockchain Technology; Disruptive Technological Innovation; Profit Growth